Gli strumenti per leggere il mondo La geografia dalla scuola dell'infanzia alla scuola secondaria di secondo grado - PIOLETTI, Anna Maria (Tratti geografici - Open Access, 2020)
This book is a tool for geographic education and the teaching of geography aimed at supporting the teacher's classroom work and intended for school teachers of all levels. The training course is designed to share geography teaching practices in an interdisciplinary perspective with the aim of experimenting educational proposals through thematic workshops.